2021
DOI: 10.3389/fimmu.2020.625542
|View full text |Cite
|
Sign up to set email alerts
|

CBP Bromodomain Inhibition Rescues Mice From Lethal Sepsis Through Blocking HMGB1-Mediated Inflammatory Responses

Abstract: CREB binding protein (CBP), a transcriptional coactivator and acetyltransferase, is involved in the pathogenesis of inflammation-related diseases. High mobility group box-1 protein (HMGB1) is a critical mediator of lethal sepsis, which has prompted investigation for the development of new treatment for inflammation. Here, we report that the potent and selective inhibition of CBP bromodomain by SGC-CBP30 blocks HMGB1-mediated inflammatory responses in vitro and in vivo. Our data suggest that CBP bromodomain inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…40,41 The role of CBP in cancer, tissue fibrosis, and stem cell differentiation has attracted widespread research interest, [42][43][44][45][46] and studies have demonstrated the involvement of CBP in regulating inflammation. 39 In the present study, ICG-001 injections effectively blocked the binding of β-catenin to CBP and decreased β-catenin activity, notably reducing the inflammation levels and alleviating inflammation-induced pathological lung injury in septic mice. Therefore, it can be deduced that the β-catenin/CBP signaling axis participates in regulating sepsis-induced inflammatory lung injury.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…40,41 The role of CBP in cancer, tissue fibrosis, and stem cell differentiation has attracted widespread research interest, [42][43][44][45][46] and studies have demonstrated the involvement of CBP in regulating inflammation. 39 In the present study, ICG-001 injections effectively blocked the binding of β-catenin to CBP and decreased β-catenin activity, notably reducing the inflammation levels and alleviating inflammation-induced pathological lung injury in septic mice. Therefore, it can be deduced that the β-catenin/CBP signaling axis participates in regulating sepsis-induced inflammatory lung injury.…”
Section: Discussionsupporting
confidence: 51%
“…CBP is a transcriptional coactivator and a functional homologue of p300; it possesses histone acetyltransferase activity, 39 which enables it to acetylate histones, non-histones, and various transcription factors. In addition, CBP can regulate the expression of target genes through interactions with transcription factors; thus, it participates in biological processes such as cell differentiation and embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…SGC-CBP30, a potent inhibitor of the highly selective CBP/p300 bromodomain, has shown therapeutic potential in a variety of diseases, including cancers, gastrointestinal syndromes, sepsis, and organ fibrosis 62 , 71 73 . We investigated the pharmacological effects of SGC-CBP30 in ALF for the first time and confirmed that pharmacological inhibition of Ep300 could effectively inhibit D/L-induced ALF in mice and ameliorate liver injury, coagulation abnormalities, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…HE scores were calculated by light microscopic analysis of four parameters including alveolar septal thickness, interstitial edema, infiltration of inflammatory cells, and alveolar congestion/collapse. Each parameter was categorized into four grades: 0 = normal; 1 ≤ 25%; 2 = 25-50%; 3 = 50-75%; and 4 ≥ 75%, and the mean score of the four parameters was used to represent the overall lung injury (25). Histopathological images were captured and analysis by using light microscope at 400x magnification (EVOS FL Auto Cell Imaging System, USA).…”
Section: Histopathological Assessment and The Measurement Of Lung Wet...mentioning
confidence: 99%